The Impact of Reaction Parameters on Graphene-like Material Synthesized Using Chemical Vapour Deposition - Lee, H.C. (Elsevier Ltd, 2017)
The remarkable properties of graphene have directly accelerated the graphene research. Due to its unique and remarkable characteristics, graphene can be potentially used in various applications. Chemical Vapour Deposition (CVD) has been identified as a promising and important method for preparation and production of graphene due to its good film uniformity and large scale production. Herein, we demonstrated that reaction parameters including the reaction duration and reaction temperature could affect the quality, quantity and morphology of synthesized samples. Energy Dispersive X-ray (EDX) results indicated that the carbon content on the graphene-like samples increased with the increasing reaction duration. Scanning electron microscopy (SEM) images showed that thicker carbon clusters were grown when a longer reaction time was used. X-ray diffraction (XRD) pattern indicted carbon existed in the samples synthesized. The comparison between different reaction parameters can assist in selecting the optimum growth parameters of graphene-like samples. © 2017 The Authors.